Vertical and horizontal variability in airborne nanoparticles and their exposure around signalised traffic intersections. (July 2016) - Goel, Anju; Kumar, Prashant
Abstract: We measured size–resolved PNCs in the 5–560 nm range at two different types (4– and 3–way) of TIs in Guildford (Surrey, UK) at fixed sites (∼1.5 m above the road level), sequentially at 4 different heights (1, 1.5, 2.5 and 4.7 m), and along the road at five different distances (10, 20, 30, 45 and 60 m). The aims were to: (i) assess the differences in PNCs measured at studied TIs, (ii) identify the best fit probability distribution curves for the PNCs, (iii) determine vertical and horizontal decay profiles of PNCs, (iv) estimate particle number emission factors (PNEFs) under congested and free–flow traffic conditions, and (v) quantify the pedestrian exposure in terms of respiratory deposition dose (RDD) rates at the TIs. Daily averaged particle number distributions at TIs reflected the effect of fresh emissions with peaks at 5.6, 10 and 56 nm. Despite the relatively high traffic volume at 3–way TI, average PNCs at 4–way TI were about twice as high as at 3–way TI, indicating less favourable dispersion conditions. Generalised extreme value distribution fitted well to PNC data at both TIs. Vertical PNC profiles followed an exponential decay, which was much sharper at 4–way TI than at 3–way TI, suggesting ∼40% less exposure for people at first floor (4.7 m) to those at ground floor around 4-way TI. Vertical profiles indicated much sharper (∼132–times larger) decay than in horizontal direction, due to close vicinity of road vehicles during the along-road measurements. Over an order of magnitude higher PNEFs were found during congested, compared with free–flow, conditions due to frequent changes in traffic speed. Average RDD rate at 4–way TI during congested conditions were up to 14–times higher than those at 3–way TI (0.4 × 10 11 h −1 ). Findings of this study are a step forward to understand exposure at and around the TIs. Graphical abstract: Highlights: Traffic intersections (TI) are pollution hotspots but exposure analysis is limited. Vertical and horizontal decay in particle number concentration (PNC) at TIs noted. Characteristic dispersion height at 3-way TI was 3.2-times higher than at 4-way TI. PNC emission factor in congested driving were up to 10-times of those in free-flow. Generalised extreme value fitted well to frequency distribution of PNC at both TIs. Abstract : Emissions of PNCs at traffic intersections is over an order of magnitude higher during congested "red traffic light" compared with free flow "green traffic light" conditions.